Identificación del riesgo biológico en el personal de enfermería del hospital básico del Empalme. - Pazmiño Zambrano, Fray Darlin (2017)
This study was carried out in the basic splicing hospital in which risks at the nursing site were identified through the application of the Triple Criteria Risk Matrix (INSHT), concluding that there is a significant risk, which was assessed for Knowing the biological action level (NAB) and the biological exposure limit (LEB), for which the biological risk assessment methodology is used BIOGAVAL is a practical procedure and is recommended to evaluate the biological risk in work activities In addition to establishing the level of biological risk and in case of taking corrective measures. As a result of the research it was established that the biological agents involved are hepatitis A virus, B virus, HIV virus, tuberculosis virus and influenza virus, based on the results obtained in the present study Proposes to apply the hygienic measures established by the methodology to minimize the level of biological risk to which each of the health workers of the present study are exposed. It can be determined that compliance with a health surveillance plan helps reduce exposure to biological agents. Key words: NAB, LEB.